Scaffolding wiki‐supported collaborative learning for small‐group projects and whole‐class collaborative knowledge building. (12th April 2016) - Lin, C‐Y.; Reigeluth, C.M.
Abstract: While educators value wikis' potential, wikis may fail to support collaborative constructive learning without careful scaffolding. This article proposes literature‐based instructional methods, revised based on two expert instructors' input, presents the collected empirical evidence on the effects of these methods and proposes directions for future refinements. The instructional methods were implemented by an expert instructor teaching a 12‐week 68‐student undergraduate design class in Canada. Data were collected from observations, interviews and content analysis of wikis. The findings revealed that in small‐group project (SGP), the wiki instructional methods enhanced collaborative learning with most instructional methods derived from cooperative learning, but in whole‐class collaborative knowledge building (CKB), the wiki instructional mehtods failed to turn the class into a self‐sustained learning community after the scaffolding faded. We conclude that the genre of wikis should be different for SGP and CKB. While the students easily adopted the 'reproduced' genre of wikis for SGP with familiar tasks, they felt overwhelmed or resistant to the unfamiliar 'emergent' genre of wikis for CKB in massive collaborative constructive learning. Therefore, we propose that future refinements for wiki‐supported CKB should focus on providing students scaffolding for intersubjectivity (understanding collaborative constructive learning) and transfer of responsibility (developing autonomy).